One Stop Centre for the survivors of sexual and gender-based violence at Juba Teaching Hospital - Busiri Julius Korsuk (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
The One Stop Centre at Juba Teaching Hospital offers a package of services for the survivors of sexual and gender-based violence. These include diagnosis and treatment of gender-based violence (GBV)-related injuries and clinical management of rape (CMR), psychological first aid (PFA), and counselling as well as legal support. The Centre provides a safe space, under one roof, for women, men, boys, and girls to obtain professional help and so be able to start healing and re-integrating into their communities.